2017
DOI: 10.1021/acsinfecdis.7b00108
|View full text |Cite
|
Sign up to set email alerts
|

Teixobactin and Its Analogues: A New Hope in Antibiotic Discovery

Abstract: Increasing bacterial resistance against current antibiotics and lack of new molecules to combat bacterial resistance are key challenges to global health. There is, therefore, a continuing need to develop new antibiotics. Teixobactin, a cyclic undecapeptide, displays excellent antibacterial activities against a range of pathogenic bacteria, such as methicillin-resistant Staphylococcus aureus (MRSA) and Mycobacterium tuberculosis. Interestingly, it operates by multiple modes of actions and is bactericidal toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 11 publications
0
35
0
2
Order By: Relevance
“…Subsequent in vitro analyses revealed that teixobactin binds to the highly conserved pyrophosphate motifs of multiple bacterial cell-wall substrates,for example,lipid II, aprecursor of peptidoglycan, and lipid III, ap recursor of cell-wall teichoic acid. [146] Va rious groups have pursued the total synthesis of teixobactin and its corresponding analogues.A dditionally, NMR and crystallographic studies have given insight into the structural details of the peptide and identified the macrolactone ring to be essential for pyrophosphate binding and thus the antibiotic effect (all of this is summarized excellently by Guo et al [147] and Fiers et al [148] ). [144] Further comprehensive studies revealed that the synergistic inhibition of both peptidoglycan and teichoic acid synthesis results in cell-wall damage,d elocalization of autolysins,a nd ultimately cell lysis.…”
Section: Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent in vitro analyses revealed that teixobactin binds to the highly conserved pyrophosphate motifs of multiple bacterial cell-wall substrates,for example,lipid II, aprecursor of peptidoglycan, and lipid III, ap recursor of cell-wall teichoic acid. [146] Va rious groups have pursued the total synthesis of teixobactin and its corresponding analogues.A dditionally, NMR and crystallographic studies have given insight into the structural details of the peptide and identified the macrolactone ring to be essential for pyrophosphate binding and thus the antibiotic effect (all of this is summarized excellently by Guo et al [147] and Fiers et al [148] ). [144] Further comprehensive studies revealed that the synergistic inhibition of both peptidoglycan and teichoic acid synthesis results in cell-wall damage,d elocalization of autolysins,a nd ultimately cell lysis.…”
Section: Reviewsmentioning
confidence: 99%
“…[145] Thel ack of resistance development so far is ar esult of the multifacetted MoA, combined with the fact that teixobactin addresses ah ighlyconserved non-protein target. [146] Va rious groups have pursued the total synthesis of teixobactin and its corresponding analogues.A dditionally, NMR and crystallographic studies have given insight into the structural details of the peptide and identified the macrolactone ring to be essential for pyrophosphate binding and thus the antibiotic effect (all of this is summarized excellently by Guo et al [147] and Fiers et al [148] ). In-depth structureactivity relationship (SAR) studies,e specially aiming to replace the synthetically inconvenient l-allo-enduracididine (l-allo-End) amino acid, led to the identification of various potent derivatives,i ncluding d-Arg 4 -Leu 10 -teixobaction ( Figure 6).…”
Section: Reviewsmentioning
confidence: 99%
“…Zudem schlugen alle bisherigen Bemühungen, Te ixobactin-resistente Mutanten von S. aureus und M. tuberculosis im Labor zu erzeugen, fehl, was die potentielle Anwendung als therapeutisches Agens bestärkt. [148] Umfangreiche Studien zu Struktur-Wirkungs-Beziehungen (SARs) versuchten insbesondere die präparativ schwer zugängliche Aminosäure l-allo-Enduracididin (l-allo-End) zu ersetzen. Anschließende Invitro-Analysen zeigten, dass Te ixobactin an das hochkonservierte Pyrophosphat-Motivv erschiedener bakterieller Zellwandsubstrate bindet.…”
Section: Teixobactinunclassified
“…[147] und Fiers et al zusammengefasst. [148] Umfangreiche Studien zu Struktur-Wirkungs-Beziehungen (SARs) versuchten insbesondere die präparativ schwer zugängliche Aminosäure l-allo-Enduracididin (l-allo-End) zu ersetzen. Dadurch konnten verschiedene potente Derivate erhalten werden, wie d-Arg 4 -Leu 10 -Teixobaction (Abbildung 6).…”
Section: Teixobactinunclassified
“…Octreotide is synthetic analogue of somatostatin consisting of eight AARs; it causes constriction of splanchnic blood vessels and this way reduces the portal pressure and gastric mucosal blood flow as well. The cyclic peptide antibiotics are, e.g., vancomycin, teixobactin, and daptomycin. Vancomycin is a glycopeptide antibiotic, teixobactin is a peptide‐like secondary metabolite, and daptomycin is a lipopeptide antibiotic.…”
Section: Introductionmentioning
confidence: 99%